Mental health literacy and psychological outcomes in dual-career athletes - Usenik, Janja; Kranjec, Eva (Frontiers in Sports and Active Living, 2025)
IntroductionDual-career athletes experience the unique challenges of balancing sporting, academic, and vocational pursuits, which can strain their well-being and increase psychological distress. This study examined the mental health of Slovenian dual-career athletes, including the prevalence of anxiety, depression, and overall well-being, as well as their mental health literacy and its potential relationship with psychological distress and well-being.Methods219 Slovenian dual-career athletes (58% female; age 15–29) completed self-report measures of anxiety (GAD-7), depression (PHQ-9), and mental well-being (WHO-5), alongside the Slovenian version of the Mental Health Literacy Scale (S-MHLS). Point and lifetime prevalence of mental health problems were assessed. Multiple regression analyses were employed to examine group differences and predictors of mental health outcomes.ResultsModerate to severe symptoms of anxiety and depression were reported by 22% and 23% of athletes, respectively, while 43% scored below the threshold for positive mental well-being. Female athletes reported significantly poorer mental health across all indicators. Regression analyses showed that greater knowledge about where and how to seek mental health information predicted lower levels of anxiety and depression and higher well-being. In contrast, more stigmatizing attitudes were linked to higher psychological distress.DiscussionThese findings suggest that improving athletes’ mental health literacy could help protect their well-being in the dual-career context. Tailored strategies to promote help-seeking and reduce stigma, while considering gender and the demands of dual careers, may be crucial for enhancing young athletes’ psychological well-being and creating more supportive environments.